Human Development in the Context of Nepal - Dulal, Tulasa Devi (Journal of Population and Development, 2021)
This article tries to highlight the condition of human development in the contest of Nepal. The topic is framed as part of the general issue of gender, caste/ethnicity, regional rural and urban disparities. This study is based on descriptive as well as analytical in nature. Sources of information in this study are secondary nature like published and unpublished research papers, human development annual reports and national and international journal articles. Data are presented in to tabular form and they are analyzed in to descriptive form. The first Human Development Report was launched in 1990 by the Pakistani economist Mahbub ul Haq and Indian Nobel laureate Amartya Sen. Since then reports have been released most years, and have explored different themes through the human development approach, which places people at the center of the development process. Since 1990, the United Nations Development Programme (UNDP) has published a series of annual Human Development Reports (HDRs) in which the human development index (HDI) is computed for each country. Nepal has been publishing the Nepal Human Development Report since 1998, with the focus shifting considering the needs of the country. In the 1990-2018 period, Nepal’s human development index score rose from 0.380to 0.579, an increase of 52.6 percent and life expectancy at birth increased by 16.1 years to 70. 5 years. Notable progress in human development has taken place in Nepal. However, across gender, region and local groups, large disparities persist.